Knowledge, attitudes and practices on cervical cancer screening among the medical workers of Mulago Hospital, Uganda - Mutyaba,Twaha; Mmiro,Francis A.; Elisabete, Weiderpass (BMC medical education, 2006)
Cervical cancer is the commonest cancer of women in Uganda. Over 80% of women diagnosed in Mulago national referral and teaching hospital, the biggest hospital in Uganda, have advanced disease. Pap smear screening, on opportunistic rather than systematic basis, is offered free in the gynaecological outpatients clinic and the postnatal/family planning clinics. Medical students in the third and final clerkships are expected to learn the techniques of screening. Objectives of this study were to describe knowledge on cervical cancer, attitudes and practices towards cervical cancer screening among the medical workers of Mulago hospital.